2008
DOI: 10.1016/j.entcs.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Expressivity in the κ Family

Abstract: In this paper we study implementation of κ calculus into nanoκ calculus -called self-assembling of κ in nk. The former is a model for molecular biology that rewrites graphs of molecules in one step; the latter is a calculus similar to κ that only admits binary interactions. We give a solution of the self-assembling of κ in nanoκ that is divergent and we show the nonexistence of deterministic solutions retaining "reasonable" properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Actually, our initial motivation for studying the expressive power of synchronizations has been the implementation of biologically inspired languages in pi calculus. In [13], we demonstrated that it is not possible to implement the κ-calculus into one admitting at most two reactants. In that paper, the expressive power was demonstrated by analyzing the models of a biologically relevant reaction (the homeo-trimerization).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, our initial motivation for studying the expressive power of synchronizations has been the implementation of biologically inspired languages in pi calculus. In [13], we demonstrated that it is not possible to implement the κ-calculus into one admitting at most two reactants. In that paper, the expressive power was demonstrated by analyzing the models of a biologically relevant reaction (the homeo-trimerization).…”
Section: Introductionmentioning
confidence: 99%